Treading Toward Anterolateral Skull Base by Unlocking the Frontotemporal Dural Fold Along with Extradural Clinoidectomy: Translation from A Cadaver to Clinical Scenario - Srivastava, Arun; Mishra, Shashwat; Kumar, Ashutosh; Nangarwal, Bhavan; Das, Kuntal; Bhaisora, Kamlesh; Verma, Pawan; Jaiswal, Awadhesh; Behari, Sanjay (Neurology India, 2021)
Background and Introduction: Unlocking of the frontotemporal dural fold (FTDF) and extradural removal of the anterior clinoid process (EACP) are challenging but mandatory skills for micro-neurosurgeons. Despite the presence of an extensive body of literature on this subject, the translation of this cadaveric and 3D simulation to a real patient turns out to be a very demanding and difficult task. Objective: This video is aimed to address the surgical nuances and major adjustments necessary in the unlocking of the FTDF and extradural ACP removal in an actual case for an early-career neurosurgeon. Surgical Technique: A 40-year lady presented with features of acromegaly with radiological evidence of significant component of the tumor in the right cavernous sinus along with sellar suprasellar component. To achieve a good hormonal control, a complete tumor excision was required, which was achieved with FTDF and EACP removal. The cavernous sinus was approached through the Parkinson's triangle. Results: The patient had uneventful recovery and good hormonal control at the 3-month follow-up. Conclusion: FTDF unlocking and EACP are elegant procedures and need to be learned by all neurosurgeons. This article will provide excellent teaching material for young neurosurgeons.